Pediatric rehabilitation post Guillain-Barré syndrome: a case report at Federal Medical Centre, Abeokuta - Fafolahan, Abiola O.; Olatunji, Taiwo O.; Davis, Abigail O.; Sodipo, Oladunni P.; Adeoye, Kafayat K.; Musa, Badiru O.; David, Olakorede; Jegede, Erioluwa; Musari, Titilope; Adeyemi, Blessing O.; Obadeji, Ebunoluwa M. (International Journal of Contemporary Pediatrics, 2022)
Guillain-Barre syndrome (GBS), a lower motor neuron autoimmune disease, primarily damages the myelin sheaths of the peripheral nervous system. Around the world, it is the main cause of acute flaccid paralysis. This case study's aim was to outline the physical therapy interventions provided to a patient at the Federal Medical Center in Abeokuta (FMCA) who was diagnosed of GBS. An 8-year-old child who arrived at the children emergency unit complaining of weariness, a headache and difficulty walking. This patient had physiotherapy interventions, which included free active exercises for the upper and lower limbs, grip strengthening and passive movements to all joints. Resisted active exercises and bridging was also incorporated. Patient was able to do standing and walking re-education at week 5th and 10th week respectively. Following physical therapy rehabilitation, the patient demonstrated improvements with range of motion (ROM), strength, balance, ambulation and endurance. Early referral for physical therapy, clinical compliance, commitment to home programme exercises, and support from family were all proven to significantly improve recovery.